Economical and Organizational Nature of Modern forms of Financial Entrepreneurship: an Analysis - КотляровИван Дмитриевич (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
An analysis of economical, financial and organizational nature of leasing, factoring and forfaiting demonstrates that all these forms of financial entrepreneurship have an outsourcing component. Notion of intermediary financing is proposed. A comparative analysis of these business tools has been made. A list of risks typical for providers of these services is given.